Adolescent Pregnancy and Its Problems - Karakuş, Savaş; Genç, Şerife Özlem; Güldemir, Ünsal; Okşaşoğlu, Buğra; Bütün, Celal; Yıldırım, Ali (The Bulletin of Legal Medicine, 2017)
Objective: The purpose of this study was to determine the adverse outcomes and pregnancy problems of adolescent pregnancy.Material and Method: Results of 171 adolescent pregnant between 10-19 age, who had given birth in our hospital between 2009 and 2016 were retrospective evaluated. The patients were seperated into adolescent early period (10-15 ages) and adolescent late period (>15-19 age). Babies,with birth weigt under 2500 gr were evaluated as low-birth-weight baby. The rates of gestational weeks, pregnancy history, preterm birth, Intrauterine mort fetüs (IUMF), preterm premature rupture of membranes (PPROM), preeclampsia and mode of delivery of groups were determined.Results: The age average of adolescent early period were determined as 14,6 ± 0,5, and the age average of adolescent late period were determined as 17,7 ± 0,5. In 3 cases (37.5 %) of adoscent early period and in 66 cases (40.5%) of adoscent late period were preterm birth  and in adoscent early period were IUMF, PROM and preeclampsia without determination. Preeclampsia were determined in 5 cases (2.9%) IUMF, in 6 cases (3.7%) PPROM and in 4 cases (2.5%) in adolescent late period were. There was no significant difference in pregnancy weeks, obstetrical history, birth-weight and preterm delivery between two groups at birth.Conclusion: Because of Births, which come true during the adolescent period, create a serious problem by formation of healthy generations; it is a problem which have to be tackle carefully. Studies, which will done with large groups of adolescent pregnancy will give more informations on this topic.
Keywords: adolescent; pregnancy; pregnancy outcome